Therapeutic and prophylactic tools for sporotrichosis: Current strategies and future tendencies - Batista-Duharte, Alexander [UNESP]; Pereira, Sandro Antonio; Saraiva Freitas, Dayvison Francis; Gutierrez-Galhardo, Maria Clara; Fuentes, Deivys Portuondo [UNESP]; Carlos, Iracilda Zeppone [UNESP] (Springer Nature, 2015)
Over the past 3 decades, important progress in the therapy of fungal infections has been made. Although several chemotherapeutic agents are relatively effective against the different species of the Sporothrix schenckii complex, even the primary drugs used to treat sporotrichosis are the ergosterol inhibitors: Triazole compounds, terbinafine, and amphotericin B. Despite the general effectiveness of these drugs, diverse problems remain, including chronic therapy, toxicity manifestations, and fungal resistance, which limit their use. These problems have stimulated a search for new agents that might be active against a wide range of clinical isolates, that are well absorbed after oral administration, that are widely distributed throughout body tissues, including the central nervous system, and that are relatively nontoxic. This chapter reviews the current therapy strategies for human and animal sporotrichosis and updates the more relevant strategies in study for prophylaxis and treatment.
Keywords: Antifungal drugs; Prophylaxis; Sporotrichosis; Treatment